1996
DOI: 10.1007/bf01499350
|View full text |Cite
|
Sign up to set email alerts
|

"So, what's a hate crime anyway?" Young adults' perceptions of hate crimes, victims, and perpetrators.

Abstract: Male and female young adults provided responses to open-ended questions about hate crimes. Results indicated considerable variability in their definitions, with perceptions of hate crimes differing with regard to demographic characteristics of both victims and perceivers. Victims may experience hate crimes differently because of who they are, why they are victimized, and with whom they share their experiences. In a separate study, males and females each evaluated a scenario of a hate crime perpetrated upon a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 17 publications
8
54
1
Order By: Relevance
“…That participants generally recommended longer sentences for crimes committed by White perpetrators against Black victims than for crimes committed by Black perpetrators against White victims is consistent with the results of Marcus-Newhall et al (2002) that showed this same pattern of results and with the results of Craig and Waldo (1996) that showed that individuals believed that hate crimes typically involve majority group perpetrators and minority group victims. This would tend to diminish the argument that penalty enhancement legislation for hate crimes could be misused to discriminate against minority group perpetrators who commit crimes against majority group victims compared to the reversed situation (Franklin, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…That participants generally recommended longer sentences for crimes committed by White perpetrators against Black victims than for crimes committed by Black perpetrators against White victims is consistent with the results of Marcus-Newhall et al (2002) that showed this same pattern of results and with the results of Craig and Waldo (1996) that showed that individuals believed that hate crimes typically involve majority group perpetrators and minority group victims. This would tend to diminish the argument that penalty enhancement legislation for hate crimes could be misused to discriminate against minority group perpetrators who commit crimes against majority group victims compared to the reversed situation (Franklin, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies investigating perceptions of hate crime noted that potential jurors viewed the typical hate crime as involving violence and including a member of a minority group (Craig & Waldo, 1996). However, the current studies reveal that crime that involves violence and includes a member of a minority group may not necessarily be perceived as typical enough for it to be considered a hate crime.…”
Section: General Conclusionmentioning
confidence: 74%
“…Studies have examined some of these factors as they play a role in perceptions of bias-motivated crime based on racism (i.e., gender and race of the perpetrator and victim; Craig & Waldo, 1996;Marcus-Newhall et al, 2002). However no research to date has examined extra-legal factors in a case involving biasmotivated crime based on heterosexism.…”
Section: Study Twomentioning
confidence: 97%
See 1 more Smart Citation
“…Not surprisingly, members of low-status groups, such as African-Americans, perceive more harm from hate crimes and are more supportive of hate crimes legislation than members of high-status groups (Craig & Waldo, 1996). In addition, people who report greater prejudice against groups targeted by a hate crime perceive less harm from such crimes and see little need for hate crimes legislation (Cowan, Heiple, Marquez, Khatchadourian, & McNevin, 2005).…”
mentioning
confidence: 97%